Isnad al-Hadith Sebagai Etika Maklumat Islam: Satu Pengenalan - Hj. Sulaiman, Ishak (Jurnal Usuluddin, 1997)
This article attempts to discuss the role of Isnad al-Hadith in developing the ethics of information retrievel among muslims. Particular attention is paid to the categories of the quality of Isnad al Hadith such as sahih, hasan and daif